LITERATURE REVIEW OF EMBRYONIC DEVELOPMENT EPIGENETICS: CHROMATIN MODIFICATION AND CELL PROGRAMMING - Kamila Alawiyah; Rizki Andini Nawawi; Meillisa Carlen Mainassy; Syarinta Adenina; Hamzah Alfarisi; Sternatami Liberitera (RADJA PUBLIKA, 2025)
This study aims to comprehensively examine epigenetic mechanisms in embryonic development, focusing on the role of chromatin modification and cell programming as regulators of gene expression without changes in DNA sequence. The type of study used was qualitative , with a descriptive approach through literature review, which examined scientific literature from reputable international journals such as Nature, Trends in Genetics, and The FEBS Journal published between 2015 and 2025. Data were collected through systematic searches of scientific articles using thematic and inductive analysis techniques, including theme identification, data reduction, and concept categorization. The results of the study show that DNA methylation, acetylation, and histone methylation are key factors in regulating gene expression during the zygotic genome activation (ZGA) phase and the formation of cell lineages. This process demonstrates the complex interaction between epigenetic and transcriptional factors that determine the direction of cell differentiation. In addition, similarities in epigenetic regulation principles between mammals and plants were found, indicating the conservation of biological mechanisms across species. The implications of the study